Posted by **Jonathan** on Wednesday, August 8, 2007 at 7:34pm.

Solve x^2>_2x+24

x^2-2x-24>=0

(x-6)(x+4)>=0

So as long as x>6, it works. But what about two negatives?

Try x=-5..checks...check me on that.

So it looks as if -inf<x<=-4 works, and

6<=x<inf works.

check that.

## Answer This Question

## Related Questions

- L'Hospital's Rule and Indeterminate Forms - I understand LHR can be applied to ...
- Algebra-I'm still stuck - The one-to-one function f is defined by f(x)=(4x-1)/(x...
- Calculus (Please Check) - Show that the equation x^5+x+1 = 0 has exactly one ...
- Calculus - Suppose that f(x), f'(x), and f''(x) are continuous for all real ...
- math pre calculus - Let A=(-2,INF] and B=(2,INF). FIND: a.)AUB b.)A (UPSIDE ...
- English - Which of the following is a true statement about an MLA Works Cited ...
- Art - What did the Vogel's artworks communicate about their historical interests...
- English - Which of the following is a true statement about an MLA Works Cited ...
- Art - How did plastic revolutionize the art of furniture design? A.) Designers ...
- calculus - Find the value of the constant C that makes the following function ...

More Related Questions